The genomic architecture of the passerine MHC region: High repeat content and contrasting evolutionary histories of single copy and tandemly duplicated MHC genes. (11th April 2022) - Westerdahl, Helena; Mellinger, Samantha; Sigeman, Hanna; Kutschera, Verena E.; Proux‐Wéra, Estelle; Lundberg, Max; Weissensteiner, Matthias; Churcher, Allison; Bunikis, Ignas; Hansson, Bengt; Wolf, Jochen B. W.; Strandh, Maria
Abstract: The major histocompatibility complex (MHC) is of central importance to the immune system, and an optimal MHC diversity is believed to maximize pathogen elimination. Birds show substantial variation in MHC diversity, ranging from few genes in most bird orders to very many genes in passerines. Our understanding of the evolutionary trajectories of the MHC in passerines is hampered by lack of data on genomic organization. Therefore, we assembled and annotated the MHC genomic region of the great reed warbler ( Acrocephalus arundinaceus ), using long‐read sequencing and optical mapping. The MHC region is large (>5.5 Mb), characterized by structural changes compared to hitherto investigated bird orders and shows higher repeat content than the genome average. These features were supported by analyses in three additional passerines. MHC genes in passerines are found in two different chromosomal arrangements, either as single copy MHC genes located among non‐MHC genes, or as tandemly duplicated tightly linked MHC genes. Some single copy MHC genes are old and putative orthologues among species. In contrast tandemly duplicated MHC genes are monophyletic within species and have evolved by simultaneous gene duplication of several MHC genes. Structural differences in the MHC genomic region among bird orders seem substantial compared to mammals and have possibly been fuelled by clade‐specific immune system adaptations. Our study provides methodological guidance in characterizing complex genomic regions, constitutes a resource for MHC research in birds, and calls for a revision of the general belief that avian MHC has a conserved gene order and small size compared to mammals.